2006
DOI: 10.1308/003588406x130624
|View full text |Cite
|
Sign up to set email alerts
|

Centralisation of Oesophagogastric Cancer Services: Can Specialist Units Deliver?

Abstract: INTRODUCTION Oesophagogastric cancer surgery is increasingly being performed in only centralised units. The aim of the study was to examine surgical outcomes and service delivery within a specialist unit.PATIENTS AND METHODS The case notes of all patients undergoing attempted oesophagogastrectomy between January 2000 and May 2003 were identified from a prospective consultant database. RESULTS A total of 187 patients (median age, 63 years; range, 29-83 years; M:F ratio, 3.9:1) underwent attempted oesophagogast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
2
22
0
2
Order By: Relevance
“…The in-hospital mortality rate was low (1 per cent), especially given the high incidence of gastric tube complications, and was comparable with lowest rates currently reported for open oesophagectomy by specialist units in the UK 1 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The in-hospital mortality rate was low (1 per cent), especially given the high incidence of gastric tube complications, and was comparable with lowest rates currently reported for open oesophagectomy by specialist units in the UK 1 .…”
Section: Discussionsupporting
confidence: 71%
“…Open surgical approaches have changed relatively little since their original descriptions. Improvements in patient selection, radicality of resection, perioperative care and development of specialist units 1 have optimized outcomes after open oesophagectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal decision-making in the diagnosis, treatment and support of cancer patients is increasingly associated multidisciplinary care studies overlap with evidence on the importance of caseload concentration [8][9][10][11], raising questions regarding the best approach to cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…Not all new cases of oesophagastric cancer from South East Wales were included as patients diagnosed at Merthyr Tydfil and Royal Glamorgan hospitals were not included. It was not within the remit of this study to analyse cost effectiveness; in the study by Forshaw et al 19 in one regional cancer centre, the cost of an oesophageal resection was reported to be £8070, with palliation costs varying from £1390 to £4720 according to modality. Clearly, there are several aspects to costs, not only fiscal considerations but also a possible trade-off in a deterioration of services elsewhere.…”
Section: Discussionmentioning
confidence: 97%